Pendugaan Pengaruh Tetua Betina dan Daya Gabung pada Persilangan Kopi Robusta - Wibowo, Ari; Sumirat, Ucu (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
Breeding programs need genotypic variation to make a selection and create a promising variety. Hybridization in plants produces genetic variations in the offspring to select Robusta coffee as superior planting material. The maternal-effect and combining ability help determine the next breeding strategy. This study aimed to determine the maternal effect and the combining ability on the morphological characters of branches and leaves of Robusta coffee diallel crosses. The study involved six groups of F1 offspring and their reciprocals from three parents, namely clones BP961, Q121, and BP409, which were planted singly side in the Kaliwining Experimental Garden, Jember, East Java. The estimation of female parental effect was analyzed using a t-test, and combining ability was analyzed using diallel analysis method III. The analysis results showed that the female parental effect occurred on the character of the internode length in all cross combinations and did not occur on stipule length, petiole length, leaf length, and leaf width. The parent of the cross that can be the best combiner was parent BP961 for the petiole length and leaf length, parent Q121 for stipule length and internode length, and parent BP409 for leaf width character.